2018
DOI: 10.1021/jacs.8b04975
|View full text |Cite
|
Sign up to set email alerts
|

No Structure-Switching Required: A Generalizable Exonuclease-Mediated Aptamer-Based Assay for Small-Molecule Detection

Abstract: The binding of small molecules to double-stranded DNA can modulate its susceptibility to digestion by exonucleases. Here, we show that the digestion of aptamers by exonuclease III can likewise be inhibited upon binding of small-molecule targets and exploit this finding for the first time to achieve sensitive, label-free small-molecule detection. This approach does not require any sequence engineering and employs prefolded aptamers which have higher target-binding affinities than structure-switching aptamers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 56 publications
0
67
0
Order By: Relevance
“…Aptamers are sequence-specific nucleic acids generated by the SELEX (systematic evolution of ligands by exponential enrichment) process, which recognize low molecular weight substrates, proteins, and even cells. 63 , 64 Different optical, 65 , 66 electrochemical, 67 69 and microgravimetric aptamer–ligand 70 sensing platforms (aptasensors) were developed, and their bioanalytical and biomedical applications, particularly, multiplexed aptasensor configurations, were discussed. 71 , 72 Scheme 3 shows the development of tetrahedron sensing module for the parallel detection of an aptamer–ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Aptamers are sequence-specific nucleic acids generated by the SELEX (systematic evolution of ligands by exponential enrichment) process, which recognize low molecular weight substrates, proteins, and even cells. 63 , 64 Different optical, 65 , 66 electrochemical, 67 69 and microgravimetric aptamer–ligand 70 sensing platforms (aptasensors) were developed, and their bioanalytical and biomedical applications, particularly, multiplexed aptasensor configurations, were discussed. 71 , 72 Scheme 3 shows the development of tetrahedron sensing module for the parallel detection of an aptamer–ligand.…”
Section: Resultsmentioning
confidence: 99%
“…To study the binding performance of the A10-excised aptamer, SYBR Green I (SGI) was used for label-free binding assays. [44][45][46][47][48] First, a 50 nM A10-excised aptamer was incubated with 2 mM adenosine ( Fig. 2B).…”
Section: Adenosine Specically Binds To the A10-excised Aptamermentioning
confidence: 99%
“…This finding enabled the generation of minimized structure-switching aptamers from small-molecule-binding aptamers with diverse structures. Recently, we developed an analytical method that utilizes Exo III and Exo I to achieve multiplexed small-molecule fluorescence detection ( 49 ). There, we observed that the inhibition of aptamer digestion by these exonucleases is dependent on concentration of the aptamer's target.…”
Section: Discussionmentioning
confidence: 99%